2012
DOI: 10.1111/j.1651-2227.2012.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in twenty‐year‐old Swedes in relation to birthweight and weight development during childhood

Abstract: The majority of those who were overweight/obese at 20 years of age were recruited after 5.5 years of age, and half of them in their late teens. Thus, during the preschool period, the entire population should be the target of primary prevention from overweight/obesity and, in the case of teenagers, prevention strategies should be developed for the whole population as well as treatment strategies for teenagers with established overweight/obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
5
17
0
Order By: Relevance
“…In this population-based study using longitudinal data, the prevalence of overweight/obesity was 11.5–13.7 % in childhood, and increased to 20.1 % in adolescence. These rates in childhood are comparable with rates reported in other studies from Norway and Nordic countries [ 6 , 12 , 22 , 35 ], but lower than rates from Norwegian children born after the year 2000 [ 4 , 23 ], rates reported from Southern European countries [ 2 ], and the United States [ 36 ]. For adolescents, the rates were almost twice as high as rates from Western-Norway [ 35 ], but approximately the same as those in Mid-Norway and other Nordic countries [ 12 , 22 , 37 ] and lower than rates from Southern European countries [ 2 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this population-based study using longitudinal data, the prevalence of overweight/obesity was 11.5–13.7 % in childhood, and increased to 20.1 % in adolescence. These rates in childhood are comparable with rates reported in other studies from Norway and Nordic countries [ 6 , 12 , 22 , 35 ], but lower than rates from Norwegian children born after the year 2000 [ 4 , 23 ], rates reported from Southern European countries [ 2 ], and the United States [ 36 ]. For adolescents, the rates were almost twice as high as rates from Western-Norway [ 35 ], but approximately the same as those in Mid-Norway and other Nordic countries [ 12 , 22 , 37 ] and lower than rates from Southern European countries [ 2 ].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore we consider the findings of moderate tracking coefficients from 2–4 and 5–7 years of age to adolescence to be consistent and important findings in our study. The same pattern has also been found in longitudinal studies from Sweden and Iceland [ 12 , 22 ]. Our results are similar to the results of the Swedish study, in which 60 % of children who were overweight or obese at 5.5 years, and 44 % of children who were overweight or obese at 2.5 years were also overweight or obese at 20 years of age [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…For the boys 76% had overweight or were obese whereas for the girls this was only true for 56%. In a recent population-based study in Sweden it was found that 17% of boys and 18% of girls 15 years old had overweight or were obese [59]. The increase in incidence for SCFE has been proposed in Scotland to be linked to an increase in BMI among children [60].…”
Section: Discussionmentioning
confidence: 99%
“…From the MUSP cohort, Mamun et al [ 33 ] reported a positive association between postnatal weight gain (1 g/day in the first six months of life) and overweight at 5 and 14 years of age. In a recent study, any significant association between weight gain during 0–1 years or 1–2.5 years and obesity in young adults was not found [ 14 ].. McCarthy et al [ 15 ] conducted detailed analyses from anthropometric measures at 14 time-points from birth to 5 years and then at 25 years of age, and found a positive association between infant growth and BMI at 25 years. However, weight gain between 21 months and 5 years (β = 0.99, P < 0.001) predicted a stronger association than between 0 and 5 months (β = 0.43, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%